The Effect of Powtoon Media for Teaching Writing Descriptive Text at Seventh Grade of SMP Swata Cinta Rakyat 3 Pematangsiantar - Saragih, Ria Angelina; Damanik, Bernieke Anggita Ristia; Sinaga, Asima Rohana (Universitas Pahlawan Tuanku Tambusai, 2024)
This research investigates the use of Powtoon as a teaching media to enhance students' writing skills in descriptive text. The primary objective is to assess the impact of Powtoon on students' writing abilities. It is posited that Powtoon serves as a powerful tool for classroom engagement. The study employs a quasi-experimental design involving two classes: the experimental group utilizing Powtoon media and the control group relying on conventional teaching methods. The sample consisted of 50 students, with 25 in class VII-2 as the experimental group and 25 in class VII-3 as the control group. Data collection involved writing tests administered before (pre-test) and after (post-test) the intervention. The research utilized Brown’s writing assessment rubric, focusing on aspects such as identification and description. The findings revealed that the mean score for the experimental group increased from 41 in the pre-test to 77.8 in the post-test, while the control group showed a rise from 35.8 in the pre-test to 68.8 in the post-test. The t-test result was 2.52, indicating a significant improvement in the writing skills of students who used Powtoon media compared to those in the control group. These results support the hypothesis that Powtoon media significantly enhances writing skills among seventh-grade students at SMP Swasta Cinta Rakyat 3 Pematangsiantar. The research recommends that educators consider integrating digital platforms like Powtoon into language learning and suggests further exploration of its applications in educational settings.